Microstructure and electromagnetic properties of Li0.65Fe1.6Ti0.5Zn0.2Mn0.05O4−Bi2O3−ZrO2 composite ceramics - Nikolaeva S. A. Svetlana Andreevna; Lysenko E. N. Elena Nikolaevna; Nikolaev E. V. Evgeny Vladimirovich; Vlasov V. A. Vitaliy Anatolievich; Surzhikov A. P. Anatoly Petrovich (2023, 2023)
Title screen